Islamic civilization : its foundational beliefs and principles - Maudoodi, Syed Abul ʻAla, 1903-1979 (Maudoodi, Syed Abul ʻAla, 1903-1979. Essential Mawdudi series., 2013)
This book attempts to bring out the vital relationship between the concept of civilization and Islam's underlying worldview and vision.